Pengaruh Green Accounting, Good Corporate Governance, dan Ukuran Perusahaan terhadap Kinerja Keuangan - Evi Sofia Inayah Wulandari; Retno Yulianti; Indah Kartika Sandhi (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to obtain empirical evidence regarding the influence of green accounting, independent boards of commissioners, boards of directors, audit committee financial expertise, institutional ownership, managerial ownership, and firm size on the financial performance of energy sector companies listed on the Indonesia Stock Exchange for the period 2021–2024. Method: This study uses a quantitative approach with multiple linear regression analysis as a data analysis tool. The research population consists of all energy sector companies listed on the Indonesia Stock Exchange for the period 2021–2024. The research sample consists of 188 observations selected using purposive sampling based on specific criteria according to the research needs. Finding: The results show that the board of directors, managerial ownership, and firm size have a significant positive effect on financial performance. Independent boards of commissioners do not have a positive effect on financial performance. Green accounting, the financial expertise of audit committees, and institutional ownership do not affect financial performance. Novelty: The novelty of this study lies in the comprehensive use of five good corporate governance indicators and its focus on the 2021–2024 period in the context of energy transition. This study also examines the relationship between green accounting, corporate governance, and firm size on financial performance to address the inconsistency of previous studies.